Liver injury possibly related to drug interaction after liver transplant: a case report. (24th March 2014) - Zhu, L. Q.; Jiang, W. T.; Pan, C.; Liu, Y. H.; Thian, Y.
Summary What is known and objective Drug‐induced hepatotoxicity is potentially lethal. Liver transplant patients receive a large number of medications and adverse drug reactions, and drug–drug interactions must be closely monitored. Case summary We report a case of a 29‐year‐old liver transplant patient who suffered liver injury most likely induced by drug interaction between capecitabine and warfarin. Vitamin K1 caused skin rash possibly because of the distribution and metabolism characteristic of the drug in this patient. What is new and conclusion Close monitoring and prompt discontinuation of the drugs with high volume of distribution and metabolized through the liver are necessary to avoid drug–drug interaction in liver transplant patients.